Report on activities for ILY in the Republic of Trinidad and Tobago - Trinidad and Tobago. Committee for International Literacy Year (Ministry of Education, 1991)
This a record of the achievements/activities of the Trinidad and Tobago Committee for International Literacy Year during the period January to December 1990.
Keywords: International Literacy Year